Alteration of MCP-1 and MMP-9 in Aqueous Humor Is Associated with Secondary Glaucoma in Fuchs Uveitis Syndrome. (18th May 2020) - Bauer, D.; Kasper, M.; Walscheid, K.; Koch, J. M.; Müther, P. S.; Kirchhof, B.; Heiligenhaus, A.; Heinz, C.
ABSTRACT: Purpose: To analyze changes in concentrations of pro- or anti-inflammatory cytokines, chemokines, or metalloproteinases (MMP) in the aqueous humor (AH) in Fuchs uveitis syndrome (FUS) patients with (FUSwG) or without (FUSwoG) secondary glaucoma. Methods: AH samples were collected from 43 eyes of Caucasian subjects (FUSwoG: n = 11; FUSwG: n = 8; control eyes: n = 24). Concentrations of IL-8, MCP-1, MMP-1, -2, -3, -9, SAA, TGFß-1, -2, -3, and TNF-α were measured by multiplex bead assay analysis. Results: Compared with the control group, levels of IL-8, MCP-1, MMP-3, and MMP-9 in the AH were significantly increased in FUSwG and FUSwoG patients. In contrast to FUSwoG patients, MCP-1 and MMP-9 level were lower in FUSwG, while expression of MMP-2, MMP-3, and TGFβ-1 was increased. Conclusion: In our experiments, glaucoma in FUS patients was associated with low levels of MCP-1 and MMP-9 in the AH, while expression of MMP-2, MMP-3, and TGFβ-1 increased. The alteration in these molecular patterns may contribute to the development of glaucoma in FUS.